Spectrum of teaching styles in the Czech Republic - Šafaříková, Jana; Tůma, Martin; Ashworth, Sara (Acta Universitatis Carolinae. Kinanthropologica, 2015)
The AIESEP International Conference, June 9–12, 2016, sponsored by the University of Wyoming in Laramie, will celebrate the 50th anniversary of the “Spectrum of Teaching Styles”. Although this pedagogical theory was first published in 1966 by Muska Mosston, it has continuously influenced and internationally contributed to the field of Physical Education. The 50th anniversary celebration is an appropriate occasion to briefly acknowledge the history of the Spectrum’s international journey. The following historical account acknowledges the introduction and influence of the Spectrum in the former Czechoslovakia, beginning in 1971 and continuing into the Czech Republic era. The first section of this article acknowledges the contributions of the Spectrum and its international acceptance. The second section focuses on Prague and the active role of the many scholars who studied, implemented, and researched the Spectrum. The third section presents some teaching style research results conducted by Faculty of Physical Education and Sport, Charles University (UK FTVS).
Keywords: věda; dějiny 21. století; Česká republika; Fakulta tělesné výchovy a sportu Univerzity Karlovy; výzkum; Teaching; mezinárodní spolupráce; tělesná výchova; lidé; spektra didaktických stylů; Czech Republic; International Cooperation; vyučování; History, 21st Century; dějiny 20. století; Physical Education and Training; Humans; Science; History, 20th Century; sjednocující model; Research